Studies on pollination ecology and seed development in black cumin (Nigella sativa) - K. RAJANI; S.S. PARIHAR; S.K. LAL (Seed Research, 2026)
Black cumin (Nigella sativa) is an annual flowering plant and its seeds are commonly known as black cumin and kalonji. The flower of this crop basically shows a unique mechanism to ensure self pollination, although abundant pollinators also visit flowers. Seed development is an important event which determines the quality of seed being harvested. The aim of this study was to study the pollination ecology and seed development and maturation under Delhi conditions. It was observed that many pollinators visited flowers and the most common visitor was Apis florea fabricius, followed by Apis cerana cerana fabricius and A. dorsata dorsata fabricius. The present study revealed that black cumin was able to produce seeds under open condition (T), under selfing (T₁) and by hand pollination of emasculated flowers (T₂). The seed yield of 8.46, 8.10 and 7.83 g/plant was obtained in the treatments To T, and T₂, respectively. Seed development and maturation, onset of germination, desiccation tolerance and period required for seed maturation was also studied. The onset of germination took place after 35-40 days of pollination, while acquisition of desiccation tolerance took place 40-45 days after pollination when the seeds attained harvestable maturity.